Back Cover Picture: Biotechnology Journal 10/2019. Issue 10 (4th October 2019) - Paganini, Carolina; Capasso Palmiero, Umberto; Pocsfalvi, Gabriella; Touzet, Nicolas; Bongiovanni, Antonella; Arosio, Paolo
Abstract : The cover represents one of the most urgent needs in the field of extracellular vesicles: a scalable and standardized process to produce vesicles with high yield and reproducible qualities. In article1800528 . Carolina Paganini, Umberto Capasso Palmiero, Gabriella Pocsfalvi, Nicolas Touzet, Antonella Bongiovanni, and Paolo Arosio summarise the state of the art and discuss how current industrial bioprocesses can serve as models to achieve this goal.